THE ROLE OF LOCAL GOVERNMENTS IN EMPOWERING MSMES THROUGH THE PEOPLE'S BUSINESS CREDIT PROGRAM IN WEST JAVA PROVINCE (Study Based on Business Law) - Edi Sofwan; Haryono Haryono; Amiludin Amiludin; Muhammad Asmawi (Universitas Muhammadiyah Tangerang, 2021)
The purpose of this study is to find, describe, and analyze the role of local governments to empower MSMEs through the KUR Program in West Java Province. This by the Regional Government is solely for the benefit of the West Java people by empowering existing MSMEs, namely through the People's Business Credit Program, which was launched by the Central Government. This research is qualitative. This research was conducted with a descriptive approach because the results obtained from this study are expected to provide a comprehensive and systematic description of the role of the West Java Regional Government in empowering Micro, Small, and Medium Enterprises. The results of this research can be useful in developing Business Law, especially related to increasing MSME Empowerment and applied in the form of providing People's Business Credit through national banks, with the hope that the Welfare of the People or the West Java Community through MSMEs will be realized soon. So that welfare is not only enjoyed by entrepreneurs who have a large capital, but also the community in general.